Prolegomena to the Christian Images Not Made by Human Hands - Gogola, Matej (Studia Ceranea, 2018)
Images not made by human hands (acheiropoietai, Gr. ἀχειροποίηταιι) played a significant role in Byzantine spiritual culture and history. This paper discusses the emergence and rise of the acheiropoietai, which represented a most important and unusual element in the Byzantine Empire. The author analyses the chronological ancestors of Christian images not made by human hands, i.e. the so-called diipetes (Gr. Διιπετής), and proceeds to demonstrate the disagreements on the topic among some of the Christian Church Fathers. The imagines imperiales, i.e. effigies of Roman emperors, constituted a significant factor in the process leading to the later veneration of images not made by human hands. The most famous of the latter is the image from Edessa, also known in historiography as Mandylion of Edessa.